New combinations and lectotype designations in Asparagaceae subfam. Scilloideae - Martínez-Azorín, Mario; Crespo, Manuel B.; Dold, Anthony P.; Pinter, Michael; Wetschnig, Wolfgang (Phytotaxa, 2015)
Hyacinthaceae (Asparagaceae subfam. Scilloideae) are commonly hysteranthous or proteranthous plants, in which leaves and inflorescences usually are not present simultaneously. Consequently, to facilitate future identification, type “specimens” were sometimes prepared to combine fragments gathered at different times so as to include as many vegetative and reproductive structures as possible. However, this is not acceptable under the rules of nomenclature. We here lectotypify four species names of Hyacinthaceae for which the intended types do not conform to the ICN (Melbourne Code). Furthermore, seven new combinations are presented to transfer recently described units of Ornithogaloideae and Urgineoideae to their proper genera, characterized by distinct and consistent morphological syndromes.